ATHLETE'S ROLE IDENTITY: AN INTEGRATIVE REVIEW OF MEASUREMENT INSTRUMENTS - Silva,Walan Robert da (2020)
ABSTRACT Introduction: The identity of the role of athlete (athletic identity - AI) can be understood as an aspect of self-concept, more specifically as a cognitive structure that guides and organizes the processing of self-related information. Objective: To verify studies that have developed or validated instruments to measure AI, and to identify the psychometric properties presented by these instruments. Methods: We searched for articles in the Scopus, APA (PsycNET), Lilacs, Scielo, ScienceDirect, SPORTdiscus and Pubmed databases with the descriptors (“athletic identity” OR “social identity” OR “self-identity” OR “athlete identity”) AND (“athlete” OR “sport” OR “type of sport”) AND (“validation” OR “validity” OR “adaptation”). Results: Of the 21 studies selected for analysis, the majority was found to have employed the theoretical assumption of athletic identity of Brewer, Van Raalte & Linder (1993), while with regard to the validity process, it was ascertained that all the studies included in the review had construct validity. Conclusion: It is suggested that future studies into validation processes of instruments related to the identity of the role of athlete apply the Item Response Theory (IRT) to make the construct validation process more reliable, attaching greater importance to the items included in the instrument. In addition, it is recommended that the criterion validity process be carried out with the intention of verifying construct stability in different populations. Level of evidence II, Diagnostic studies - Investigating a diagnostic test.